Transoral laser microsurgery for glottic cancer in the elderly: Efficacy and safety. Issue 6 (12th January 2019) - Rodrigo, Juan P.; García‐Velasco, Fabian; Ambrosch, Petra; Vander Poorten, Vincent; Suárez, Carlos; Coca‐Pelaz, Andrés; Strojan, Primoz; Hutcheson, Kate; Folz, Benedikt J.; Bernal‐Sprekelsen, Manuel; Rinaldo, Alessandra; Silver, Carl E.; et al.
Abstract: Background: Data about the results of transoral laser microsurgery (TLM) in elderly patients are limited. Methods: A retrospective study of 72 consecutive cases of glottic carcinoma (63 pT1 and 9 pT2 cases) in elderly patients (≥70 years old, mean 76 years) treated with TLM was made. A systematic review of the literature was performed. Results: Six patients (8%) had postoperative complications, but no treatment‐related deaths were observed. Local recurrences occurred in 12 patients (16.5%): nine with pT1 (14%) and three with pT2 (33%) tumors. Five‐year disease‐specific survival (DSS), overall survival, and laryngectomy‐free survival were 95%, 68%, and 88%, respectively. The literature review indicated that TLM is safe and effective treatment for these patients, with few complications and good local control (>85%) and DSS (>90%) rates. Conclusions: Our results and the information from the literature show that TLM for glottic cancer in elderly patients can lead to satisfactory treatment results.